Aesthetic Encounters, Canines, and Care : New Multispecies Methodological Avenues in Organizational and Business Ethics - Huopalainen Astrid; Satama Suvi; Tallberg Linda (Springer Nature, 2025)
How can we ethically include nonhuman animals during methodological considerations in organizational and business ethics research? Additionally, what methodological opportunities and challenges do multispecies research approaches present for these research areas? Building on critical posthumanist theory, the feminist ethic-of-care tradition in animal ethics, and the aesthetics of posthuman methodologies, this article develops a novel avenue for multispecies methodological research that expands current approaches to organizational and business ethics research beyond a purely human-centric lens. Empirical materials include diary excerpts about one author’s daily ethical encounters with her dogs and video clips of dog–human relationships, along with aesthetic reflections from two other researchers. Our reflections are shaped by posthumanist theorizing and critically problematize the seemingly static, anthropocentric categorizations of researcher, positionality, and research participant within the ethically complex context of multispecies research. Beyond discussing our findings in relation to recent business ethics research, we propose a methodological avenue for studying the aesthetic hybridization of humanimal subjectivities, including subtle bodily interactions between dogs and humans. This avenue fosters more aesth-ethically attuned and species-inclusive research methodologies in animal organization studies (AOS) and the broader fields of business ethics and organization studies, which are especially critical in the Anthropocene.